Access and usage of Internet in Agricultural institutions - Lakshmi Murthy (Journal of Agricultural Extension Management, 2025)
Advances in Information and Communication technologies (ICTs), particularly Internet technologies have changed the mechanism of information access and dissemination. ICTs have impacted all sectors including the agriculture sector. These technologies provide effective ways to transfer information, improve information management and meet information needs more effectively. New tools are increasing the ability to access, store, process and disseminate information and giving a mechanism for sharing of information resources in a faster and more effective manner.